PENAMBAHAN TRAKSI MANUAL PADA PEMBATASAN LINGKUP GERAK SENDI (LGS) DENGAN INTERVENSI ULTRASOUND (US) DAN RANSCUTANEOUS ELECTRIKAL NERVE STIMULATION (TENS) DAPAT MENINGKATKAN LINGKUP GERAK SENDI (LGS) ROTASI INTERNAL PADA PASIEN FROZEN SHOULDER - Jaya Negara, I Made Hartha (Majalah Ilmiah Fisioterapi Indonesia, 2013)
Frozen shoulder is a syndrome or condition with attacks of pain and limitation of active and passive motion with an uncertain cause / idiopathic often experienced by people aged 40-60 years and had a history of trauma. Causes for auto immobilization response to local tissue damage results repetitive injury, diabetes mellitus, paralysis, post breast surgery and myocardial infarction or chest, of the glenohumeral joint (bicipitalis tendonitis, rotator cuff inflammation, fracture) or extra-articular disorders (cervical spondylisis, angina pectoris). The main purpose of writing this paper to determine the diff addition of manual traction therapy restrictions LGS, the US. and with US, TENS, TENS for the increase in internal rotation in LGS patients soulder frozen. The research was conducted at the Poly Clinic Physiotherapy Public Hospital Sanglah Denpasar and Mutiara Medika Clinic on May 2011 until September 2011. The problems examined in this study was limited range of motion due to internal sendirotasi Frozen Shoulder is measured using a Goniometer. The research was divided into two groups: a control group and treatment group. The control group was given ultrasound and TENS treatment group was given intervention ultrasound, TENS and Manual Traction in the restricted range of motion data processing and data analysis using statistical program for science program (SPSS 13.0). By hypothesis testing using the Mann-Whitney test derived p-value = 0.000 (p value <0.05) which means that there are significant differences in the mean difference between the average value of LGS internal rotation of the control group and the mean value of the difference in internal rotation of the LGS treatment groups. This suggests that the addition of manual traction LGS restrictions on U.S. intervention more effective and TENS increase LGS internal rotation in significant U.S. intervention and TENS on the condition of frozen shoulder. US intervention and TENS may provide increased internal rotation of the shoulder joint LGS meaningful on condition of frozen shoulder, it can be seen from the hypothesis testing using the Wilcoxon test p-value = 0.001 (p value <0.05). US intervention, TENS and manual traction can provide an increase in restrictions LGS, LGS significant internal rotation on the condition of frozen shoulder, it can be seen from the hypothesis testing using the Wilcoxon test p-value = 0.001 (p value <0.05). The addition of manual traction LGS restrictions on U.S. intervention more effective and TENS increase significantly LGS internal rotation rather than the intervention of US and TENS on the condition of frozen shoulder, it can be seen from the hypothesis testing using the Mann-Whitney test with p value = 0.000 (p value <0 , 05). To generate an increase in internal rotation of the shoulder joint LGS greater in the frozen state should shoulder the provision of manual traction LGS restrictions to be one obvious choice for the addition of various modalities of physiotherapy interventions.
Keywords: US, TENS, Traction Manual and LGS measured by goneometer.